2014
DOI: 10.1038/ejcn.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Sucralose enhances GLP-1 release and lowers blood glucose in the presence of carbohydrate in healthy subjects but not in patients with type 2 diabetes

Abstract: BACKGROUND/OBJECTIVE: Artificial sweeteners were thought to be metabolically inactive, but after demonstrating that the gustatory mechanism was also localized in the small intestine, suspicions about the metabolic effects of artificial sweeteners have emerged. The objective of this study was to determine the effect of artificial sweeteners (aspartame and sucralose) on blood glucose, insulin, c-peptide and glucagon-like peptide-1 (GLP-1) levels. SUBJECTS/METHODS: Eight newly diagnosed drug-naive type 2 diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 24 publications
2
61
1
8
Order By: Relevance
“…This suggests an action of other components in the cola or a learned association between cola consumption and carbohydrate challenge. One report noted sucralose enhanced GLP-1 release to a mashed potato meal and lowered the glycemic response in healthy adults, though insulin concentrations were unaffected [81]. Another report observed no effect of sucralose on GLP-1 or GIP concentrations nor an effect on gastric emptying [77].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests an action of other components in the cola or a learned association between cola consumption and carbohydrate challenge. One report noted sucralose enhanced GLP-1 release to a mashed potato meal and lowered the glycemic response in healthy adults, though insulin concentrations were unaffected [81]. Another report observed no effect of sucralose on GLP-1 or GIP concentrations nor an effect on gastric emptying [77].…”
Section: Discussionmentioning
confidence: 99%
“…This is the case in cell culture (130), but support in animal models (101) and humans has been weak. Trials have reported no effect of sucralose on plasma GLP-1 or plasma glucose (170); no effect on GLP-1 and an increase in glucose (207) a rise of GLP-1 with no effect on glucose (41) and an elevation of GLP-1 with a lower glucose concentration (255). There is no resolution of the matter at this point.…”
Section: Endocrine Responses To Carbohydratementioning
confidence: 99%
“…Only 1 study has shown a significant increase in plasma insulin responses, and interestingly there were no effects on GLP-1 or blood sugar outcomes [70] . In contrast, a later study showed that HPS enhanced GLP-1, reduced blood sugar, and had no effect on insulin responses [73] . Three studies have shown significant enhancement of GLP-1 responses with no effects on blood sugar or insulin [56,71,72] .…”
Section: T1rs May Promote Plasma Glucose Clearancementioning
confidence: 92%